2004
DOI: 10.1097/00124509-200412000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Does Electrode Placement Predict Time to Rehospitalization?

Abstract: We sought to determine whether electrode placement influenced time to rehospitalization. A retrospective review of an elderly, depressed population that had received bitemporal, bifrontal or 6 x RUL ECT was examined to determine time to rehospitalization. Bitemporal ECT was associated with a statistically significant reduction in the number of (P = 0.026) and time to (P = 0.025), rehospitalization. Bitemporal ECT may be a preferred electrode placement, not only because of its demonstrated effectiveness across … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…However, 36% of patients also had clinically identifiable cognitive side effects. 11 Heikman et al, 12 in a clinical trial showed that high-dose (5X ST) RUL ECT has a faster antidepressant effect compared with low-dose (1.0X ST) BF ECT. They recommended further studies to examine cognitive risk/benefit ratio of a higher BF stimulus dose (at least 1.5X ST).…”
mentioning
confidence: 99%
“…However, 36% of patients also had clinically identifiable cognitive side effects. 11 Heikman et al, 12 in a clinical trial showed that high-dose (5X ST) RUL ECT has a faster antidepressant effect compared with low-dose (1.0X ST) BF ECT. They recommended further studies to examine cognitive risk/benefit ratio of a higher BF stimulus dose (at least 1.5X ST).…”
mentioning
confidence: 99%
“…67 The first ECT devices produced sinusoidal pulses whereas the current devices produce brief pulses (duration of each pulse: 1-2ms) and, more recently, ultra-brief ones (duration of each pulse < 0.5ms; being common, depending on the device used, pulses of 0.25 or 0.3ms). Preliminary studies have been suggesting that right unilateral ECT with ultra-brief stimulation (RUL-UB ECT) preserves the efficacy and substantially reduces the cognitive sideeffects.…”
Section: Ect Techniques and Responsementioning
confidence: 99%
“…Although there is some research that suggests that BF ECT is clinically superior to BT ECT and to RUL ECT, 4 other studies have indicated that BF ECT is clinically equivalent to BT ECT and RUL, 5,6 and a third group of findings has suggested that BT ECT is clinically superior to BF ECT. 8,11 In addition to the research that indicates that BF ECT is at least comparable to the more traditional placements, there is also some evidence that BF ECT might actually be superior. 4 In 1993, Letemendia et al 4 randomly assigned participants to BT ECT, RUL ECT, or BF ECT conditions.…”
Section: Clinical Efficacymentioning
confidence: 99%